Redefining Project Management: Embracing Value Delivery Offices for Enhanced Organizational Performance - Saeed Moghaddasi; Kambiz Kordani; Hadi Sarvari; Amirreza Rashidi (Buildings)
This paper explores the transition from traditional Project Management Offices (PMOs) to Value Delivery Offices (VDOs), marking a shift from a process-centric to a value-centric approach in project management. Utilizing a mixed-methods research approach, the study combines quantitative data analysis with qualitative interviews and case studies from various industries. This study provides clear insights into the benefits and strategic impacts of adopting VDOs. Key findings include the pivotal role of change management in facilitating this transition and the introduction of the Value Delivery Maturity Model (VDMM) to assess value delivery progression. The paper discusses practical implications for organizations, recommends strategies for effective implementation and management of VDOs, and identifies potential challenges and solutions in the transition process. This research contributes to the evolving field of project management by highlighting the significance of value-centric approaches in contemporary business environments.